UTILIZATION OF SWINE'S VESICA URINARIA AS AN EXTRACELLULAR MATRIX FOR THE HEALING PROCESS OF OPEN WOUNDS IN WHITE MICE - Gumawan, Wayan Herry; Wirata, Wayan; Gorda, Wayan; Sudimartini, Luh Made (Buletin Veteriner Udayana, 2020)
Extracellular matrix (ECM) is currently one of the most commonly used scaffolds for tissue engineering procedures. Extracellular Matrix (ECM) can originate from the submucosa of the small intestine or vesica urinaria (urinary bladder) of a pig. The purpose of this study was to determine the suitability and safety level of using pig’s vesica urinaria as an extracellular matrix to the process of healing open wounds in white rats and to find out the changes that occurred in the implant area after administration of urine vesica powder which was observed macroscopically. Thirty-two male white rats to be used in the study were adapted environmentally for 1 week and given commercial feed (pellet brand 552) and adlibitum drinking water. Rats were divided into two groups of 12 each. Group I (treatment) of 12 rats in the back area were injured with a scalpel blade 2mm deep and 2 cm long and treated with extracellular matrix material derived from pig’s vesica urinaria. Group II (control) ie 12 treated rats were the same as group I and were not treated. Monitoring the safety of the matrix material then observing the development of wound healing at 24 hours, day 5, day 10, and day 15 postoperatively by observing macros (redness, swelling, and scab). The results of the examination showed that the administration of extracellular matrix material accelerated the wound healing process compared to the control group with a perfect closed wound mark on the 15th day.